A MEDIATING EFFECT OF DONGLE AND BROADBAND ON THE RELATIONSHIP BETWEEN USERS FACTORS AND CONNECTION IN LIBYA - Musbah, Musbah. A.; Khalifa, Nasradeen. A. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
This is a positioning paper reflecting the problem and proposed the other name of Internet is technology. It is a Global system which is interconnected with computer networks all over the world. It also uses the standard of Internet protocol suit (TCP/IP) to make a linkup with millions of computer devices globally. Internet is a web of network which interconnects millions of private, public, academic, business, and government networks, of local to global scope, that are linked by a broad array of electronic, wireless, and optical networking technologies, the aim of this study is to examining the local field data for Dongle connection and Broadband connection in for selected site and to develop a statistical relationship users and connection at selected sites as well as to validate developed a model with respect to connection at selected sites. The Internet allows greater flexibility in working hours and location, especially with the spread of unmetered high-speed connections. Internet can be accessed in anywhere by any means or medium. Internet not only be used in big screen computers or laptops but also can be used in smart phones and tablets. There are many medium or source of internet connections, but in this advance technology there are two broad sources and they are either broadband connection or dongle connection.